Navegador de Enfermeria para el cuidado y manejo en pacientes Oncologicos - Osorio-Calle, Yuli-Pilar (2022)
Objective: To analyze the development of scientific evidence on the use of the nurse navigator for the care and management of oncology patients. Materials and method: An integrative review was conducted in the databases PubMed, Science Direct Cochrane Library and Scielo of publications generated between 2011 and 2021, using the key descriptors "navigator", "nurse" "oncology" "cancer" and their respective synonyms in English and Spanish". Results: Scientific evidence highlights the need for the use of nurse navigators to promote educational actions for the management and health care of continuing and new oncology patients with the aim of sustaining self-care during the disease process. Conclusions: It is important to implement this platform in health services as a strategy of technological innovation in continuity of care, in order to avoid risk of complications in their health and to be addressed in a timely manner, to be referred to competent personnel as appropriate.